A proposed model for evaluating the financial performance of economic institutions A sample of the active institutions in the industrial zone in M sila - benelbar, moussa; BOUSSAG, AMINE (Journal of Research in Finance and Accounting, 2019)
The objective of this paper is to evaluate the financial performance of a sample of institutions active in the industrial area in M'Sila through a proposed model that includes a set of non-numerical indicators derived from financial balance indicators and financial ratios indicators. For achieve this, a survey was designed for financial department officials in the 32 institutions studied. The results of the study hypothesis that the institutions active in the industrial area under study achieved an acceptable financial performance at the level of 0.05.